Application of Sleep Hygene and Elderly Gymnastics Against Sleep Pattern Disorders in the Elderly - Melanie, Fitri; Noviani, Wulan (Rifa'Institute, 2023)
Introduction: Elderly are individuals aged 60 years and over. Sleep disturbance is a common problem that is often experienced by many elderly people. As they get older, their sleep patterns tend to change. Sleep disturbances in the elderly can be in the form of difficulty sleeping, maintaining sleep, frequent awakenings, and waking up early in the morning. The prevalence of sleep disorders in Indonesia is quite high, reaching 67%, while in the elderly it can reach up to 50% who experience some form of sleep disturbance. Objective: Of this study was to determine the application of sleep hygiene and exercise for the elderly against sleep disorders in the elderly. Method: The writing method used in this case study is a case study with a nursing care approach. Results and Discussion: Obtained after nursing care for 3 meetings were that the sleep patterns of the elderly improved as evidenced by the decrease in the results of the PSQI (Pittsburgh Sleep Quality Index) study. Conclusion: It can be concluded that the elderly who experience sleep pattern disorders can be given intervention or non-pharmacological therapy in the form of the application of sleep hygiene and elderly gymnastics